PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP UNDANG-UNDANG NO. 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH PEGAWAI NEGERI/PENYELENGGARA NEGARA - Winalda, Lian; Erlinda, Sri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : This research is motivated by many corruption cases that occur in Indonesia, one of which is Edhy Prabowo and the increasing cases of alleged bribery related to the export permit of lobster seeds to the investigation stage. The formulation of the problem in this study is how Riau University Students’ Perceptions of Law No. 20 of 2001 concerning the Eradication of Corruption Committed by Civil Servants / State Administrators. The research objective was to determine the Riau University Student Perceptions of the Law No. 20 of 2001 concerning the Eradication of Corruption Committed by Civil Servants / State Administrators. The benefits of research results for students are to provide an overview of Riau University Student Perceptions of the Law No. 20 of 2001 concerning the Eradication of Corruption Committed by Civil Servants / State Administrators. This research method is descriptive quantitative, data collection instruments are quastionnaires, interviews, and documentation consisting of 8 indicator with 45 statements. The population in this study were students of the University of Riau as many 32.436 people. The sample in this study was taken using the Qouta Sampling technique, and sampling using the Icedental Sampling as many 200 people. Based on the results of the study, it was found that the results of the average percentage value of the alternative answers to the dominant respondents were 76,39% where this range was in the Very Good category with the existence in the range 75,01% - 100%. Thus it can be concluded that the Perception of Riau University Student Against Law No. 20 of 2001 concerning the Eradication of Corruption Committed by Civil Servants / State Administrators is Very Good.Key Words: A Criminal act of Corruption